Synthesis of Pyrrolo[3,2-b]carbazole Derivatives via Palladium-Catalyzed C–H Activation - Jella, Rama Raju; Nagarajan, Rajagopal (Synthesis, 2014)
A simple method for the synthesis of different pyrrolo[3,2-b]carbazole derivatives by the reaction of 3-(acetylamino)carbazoles with various symmetrical diaryl-substituted alkynes via palladium-catalyzed C–H activation is reported.
Keywords: 3-aminocarbazoles; palladium catalysis; pyrrolo[3,2-b]carbazoles; C–H activation; diarylacetylenes